Polyphenylene sulfide composite material and preparation method thereof

By combining low-dielectric glass fiber, functionalized POSS and POE-g-GMA, blending with PA66, combining organic zirconium phosphotungstic acid, the dielectric constant and CTI problems of polyphenylene sulfide materials are solved, achieving high CTI, polyphenylene sulfide composite materials with low dielectric properties and low thermal expansion coefficient, suitable for consumer electronics field.

CN119320555APending Publication Date: 2025-01-17GUANGDONG ALDEX NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411654234.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Polyphenylene sulfide materials have problems such as high dielectric constant and linear thermal expansion coefficient and low relative trace index (CTI), which is difficult to meet the requirements for improving the dielectric performance of materials in the 5G era, and are prone to environmental pollution during use. Causes leakage and affects insulation performance.

Method used

By combining low-dielectric glass fiber, functionalized POSS, POE-g-GMA and organic zirconium phosphotungstic acid, the chemical composition and molecular structure of the glass are adjusted, the dielectric constant is reduced, and the CTI value is increased by blending PA66 with PPS , combined with the negative thermal expansion material zirconium phosphotungstate reduces the thermal expansion coefficient.

Benefits of technology

The high CTI, low dielectric properties and low linear thermal expansion coefficient of polyphenylene sulfide composite materials are achieved, and the mechanical properties and leakage resistance of the material are improved, which is suitable for the consumer electronics field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320555A_ABST
    Figure CN119320555A_ABST
Patent Text Reader

Abstract

The invention relates to a polyphenylene sulfide composite material and a preparation method thereof, and the polyphenylene sulfide composite material is prepared from the following raw materials: PPS (polyphenylene sulfite) resin, PA66 (polyamide 66) resin, low dielectric glass fiber, functionalized POSS (polyhedral oligomeric silsesquioxane), POE-g-GMA (polyhedral oligomeric silsesquioxane), organized zirconium phosphotungstate, N, N '-bis (2, 2, 6, 6-tetramethyl-4-piperidyl)-1, 3-benzenedicarboxamide, and bis (2, 6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate. The polyphenylene sulfide composite material has excellent mechanical properties, high CTI (Comparative Tracking Index), low dielectric property and low linear thermal expansion coefficient, and can be applied to the field of consumer electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a polyphenylene sulfide composite material and a preparation method thereof. Background Art

[0002] Polyphenylene sulfide (PPS) is a polymer with weakly polar crystalline molecular chains. It has excellent properties such as high rigidity, good heat resistance, high mechanical strength, chemical resistance, and good dimensional stability. Its resin dielectric constant can reach 3.3, which is the smallest dielectric loss factor among engineering plastics. However, polyphenylene sulfide has disadvantages such as high brittleness and low relative tracking index (CTI), which restrict its further application and development. Conventional use requires the addition of glass fiber reinforcement to improve its rigidity and other mechanical properties. However, the dielectric constant of conventional glass fiber is about 6.5, so the dielectric constant of PPS resin becomes larger after glass fiber reinforcement. With the development of communication technology, my country has fully opened the 5G era, and has put forward further requirements for the dielectric properties of materials (dielectric constant requirement ≤3.1). At this time, glass fiber reinforced PPS resin can no longer meet the requirements. |

[0003] During the use of electrical products, due to environmental pollution, there is dirt and moisture on the surface of the insulating material, which causes leakage, and the corrosion induced by this damages the insulation performance. Therefore, an accelerated test simulating extremely harsh conditions is designed to test whether the insulating material will form leakage traces, so as to distinguish the ability of solid insulating materials to resist leakage tracking in a short time and ensure the safety of the product under specific environmental conditions. The CTI test is to apply voltage to both ends of the platinum electrode, place the electrode on the test sample, and drip ammonium chloride solution between the electrodes, one drop every 30 seconds. When the current between the two electrodes is greater than 1A, the experiment is terminated and the number of drops of ammonium chloride added is recorded. According to the ASTM D3638 standard, the voltage at which exactly 50 drops of contaminated liquid will cause the test to fail [current greater than 1A (0.5s)] is defined as the CTI value of the material. It is generally believed that the CTI value of a material is related to its carbon forming ability, surface hydrophobicity, thermal conductivity, and the type of filler in the composite material. The stronger the carbon-forming ability, the lower the CTI. For example, polycarbonate (PC), polyphenylene oxide (PPO), and polyphenylene sulfide (PPS) have low CTI due to their strong carbon-forming ability; while the CTI of materials such as polypropylene (PP) and polyamide (PA) can reach 600V.

[0004] Generally speaking, the size or volume of most materials will gradually increase when the temperature rises, and will shrink when the temperature drops, which is the phenomenon of thermal expansion and contraction. Polymers including PPS expand when heated and have a high thermal expansion coefficient. Thermal expansion problems are generally related to the crystal morphology, electronic changes, microstructure and defects of the material. The principle of thermal expansion and contraction of materials is that the molecular movement inside the material will be affected by temperature changes. When the temperature rises, the molecular vibration amplitude in the material will increase, and the material size will also increase. The thermal expansion problem of materials often has a great impact on practical applications. The thermal expansion coefficient of inorganic particle fillers is much lower than that of high molecular polymer resins. Therefore, the thermal expansion coefficient of composite materials can be reduced by blending inorganic particles with polymer resins. Inorganic particles can fill some of the gaps in the resin matrix, increase the constraints on the resin molecular chains, and inhibit the thermal movement of its molecular chains. However, the thermal expansion coefficient of traditional inorganic particle fillers is generally positive. If you want to reduce the thermal expansion coefficient of the resin to a lower value, you often need to add a large amount of inorganic fillers to the resin matrix. Too high an addition amount will cause a significant decrease in the mechanical properties of the resin and increase the difficulty of injection molding. Inorganic ceramic fillers with negative thermal expansion properties can achieve a greater reduction in thermal expansion coefficient with a smaller addition amount, and are currently a more effective and easily controllable method for improving thermal expansion properties.

[0005] At present, some research has been done on the low dielectric PPS composite system in the prior art, for example: Chinese patent CN112679956A discloses a high-precision low-overflow low-warpage low dielectric PPS modified material and a preparation method thereof, which comprises, by weight percentage, PPS 19.6-44.2%, PPE 5%-11%, glass fiber 30-45%, mineral (I) 4-7%, mineral (II) 5-20%, toughening agent 2-5%, lubricant 0.3-0.45%, antioxidant 0.15-0.3%, halogen absorbent 0.2-0.35%, desulfurizer 0.15-0.3%, mineral (I) is selected from inorganic salt whisker material, and mineral (II) is selected from hollow microspheres. Chinese patent CN112694753A discloses a low dielectric PPS / PMP composite material and a preparation method thereof. The composite material of the present invention comprises the following components in parts by weight: 20-70 parts of polyphenylene sulfide; 10-30 parts of PMP; 10-30 parts of low dielectric glass fiber; 3-8 parts of toughening agent; 0.5-1 parts of stabilizer; 0.5-1 parts of lubricant; 1-5 parts of PFA. It can be seen from the above patents that in the current prior art, the technical effect of the low dielectric PPS composition is mainly achieved by adding low dielectric fillers (hollow glass microspheres, low dielectric glass fibers, polyhedral cage-type oligomeric silsesquioxanes, etc.) or low dielectric resins (mainly polyolefin resins). Summary of the invention

[0006] Based on this, the object of the present invention is to provide a polyphenylene sulfide composite material with excellent mechanical properties, high CTI, low dielectric properties and low linear thermal expansion coefficient, which can be applied in the field of consumer electronics.

[0007] To achieve the above object, the present invention adopts the following scheme:

[0008] A polyphenylene sulfide composite material, the composition is prepared from the following raw materials in parts by weight:

[0009]

[0010] The functionalized POSS is a functionalized polyhedral cage-type oligomeric silsesquioxane; and the POE-g-GMA is a copolymer of ethylene and octene grafted with glycidyl methacrylate.

[0011] In some embodiments, the polyphenylene sulfide composite material is prepared from the following raw materials in parts by weight:

[0012]

[0013]

[0014] In some embodiments, the polyphenylene sulfide composite material is further preferably prepared from the following raw materials in parts by weight:

[0015]

[0016] In some of the embodiments, the number average molecular weight of the PPS resin is 28,000 to 36,000; the number average molecular weight of the PA66 resin is 22,000 to 28,000; the dielectric constant (1GHz) of the low dielectric glass fiber is not higher than 4.5; the end group of the functionalized POSS contains an epoxy group; the glycidyl methacrylate grafting rate of the POE-g-GMA is 1.0 to 1.4%; and the particle size of the organic zirconium phosphotungstate is 0.5 to 3.5 μm.

[0017] In some of the embodiments, the preparation process of the organic zirconium phosphotungstate is as follows: (1) 100g of zirconium phosphotungstate is placed in a flask, and then 800-1200mL of a sodium hydroxide solution with a concentration of 0.3-0.5mol / L is added, and the mixture is stirred at 50-70°C for 1-3h. After stirring, the pH of the zirconium phosphotungstate is washed to 7 with deionized water, and the mixture is dried for use; (2) 3-5g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to 50-70mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, and then the pretreated zirconium phosphotungstate obtained in step (1) is added to the solution, stirred for 1-2h, filtered and washed, and dried at 100-120°C for 2-4h to obtain the organic zirconium phosphotungstate.

[0018] Another object of the present invention is to provide a method for preparing the polyphenylene sulfide composite material.

[0019] The preparation method of the polyphenylene sulfide composite material, specifically, the technical scheme comprises the following steps:

[0020] (1) drying the PPS resin and the PA66 resin, and then mixing with the POE-g-GMA, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate;

[0021] (2) mixing the functionalized POSS and the organic zirconium phosphotungstate;

[0022] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (e.g., the fourth zone) of the parallel twin-screw extruder (eight zones in total), and the low dielectric glass fiber is added to another side (e.g., the third zone) for melt extrusion and granulation.

[0023] In some embodiments, the drying temperature in step (1) is 80-110° C., and the drying time is 4-8 hours.

[0024] In some embodiments, the drying temperature in step (1) is 90-100° C., and the drying time is 4-6 hours.

[0025] In some embodiments, the process parameters of the parallel twin-screw extruder described in step (3) include: zone one temperature of 285-305°C, zone two temperature of 290-310°C, zone three temperature of 290-310°C, zone four temperature of 295-315°C, zone five temperature of 295-315°C, zone six temperature of 290-310°C, zone seven temperature of 290-310°C, zone eight temperature of 290-310°C, die head temperature of 290-310°C, and screw speed of 200-600rpm.

[0026] In some of the embodiments, the process parameters of the parallel twin-screw extruder described in step (3) include: zone one temperature of 290-300°C, zone two temperature of 295-305°C, zone three temperature of 295-305°C, zone four temperature of 300-310°C, zone five temperature of 300-310°C, zone six temperature of 295-305°C, zone seven temperature of 295-305°C, zone eight temperature of 295-305°C, die head temperature of 295-305°C, and screw speed of 300-500rpm.

[0027] In some embodiments, the screw shape of the parallel twin-screw extruder is a single-line screw.

[0028] In some embodiments, the ratio L / D of the screw length L to the diameter D of the parallel twin-screw extruder is 35-50.

[0029] In some embodiments, the ratio L / D of the screw length L to the diameter D of the parallel twin-screw extruder is 35-45.

[0030] In some of the embodiments, the screw of the parallel twin-screw extruder is provided with one or more (including one) meshing block areas and one or more (including one) reverse thread areas.

[0031] In some of the embodiments, the screw of the parallel twin-screw extruder is provided with two meshing block areas and one reverse thread area.

[0032] In some embodiments, in step (1) and / or step (2), a stirrer is used to perform the mixing step, and the rotation speed of the stirrer is 500-1500 rpm.

[0033] The principle of the polyphenylene sulfide composite material of the present invention is as follows:

[0034] In order to improve the defects of dielectric constant and linear thermal expansion coefficient being too high and CTI being too low in polyphenylene sulfide resin, the present invention reduces the dielectric constant of polyphenylene sulfide composite material by compounding low dielectric glass fiber, functionalized POSS and POE-g-GMA. Among them, low dielectric glass fiber belongs to a glass system with a high boron content, and has the characteristics of low density, low dielectric constant and low dielectric loss. The low dielectric glass fiber achieves the purpose of reducing dielectric constant by adjusting the glass chemical composition, reducing CaO content, increasing BO content and introducing a small amount of TiO; polyhedral oligomeric silsesquioxane (POSS) has a cage-type nanostructure, which has a large free volume, high porosity and low molecular polarizability, so the dielectric constant of POSS is 2 to 2.5 (test frequency is 1GHz); POE-g-GMA has no unsaturated double bonds in the molecule, which makes the electron cloud distribution of the molecule relatively stable. Under the action of the electric field, the electron cloud is not prone to violent displacement and polarization, so the dielectric constant is low. In addition, there are a certain amount of short side chains in the POE molecular structure, which increases the steric hindrance of the molecules and limits the close packing of the molecular chains. The gaps between the molecular chains increase, reducing the interaction between the molecules, reducing the polarization of the molecules under the action of the electric field, and thus causing the dielectric constant to decrease.

[0035] The relative tracking index (CTI) test can simulate the leakage of insulating materials during actual use due to surface dirt and moisture. Polyphenylene sulfide (PPS) is a thermoplastic material with a benzene ring in the main chain. It has a strong carbon-forming ability. The CTI of pure PPS is only 150V. It can usually be improved by adding materials with poor carbon-forming ability to form an alloy. Polyamide 66 (PA66) is a polymer material without a benzene ring in the main chain. It has poor carbon-forming ability. The CTI of pure PA is as high as 600V, and it has a certain compatibility with PPS. The CTI of PPS can be improved by blending with PPS.

[0036] Normally, the size or volume of most materials will gradually increase when the temperature rises, and will shrink when the temperature drops, which is the phenomenon of thermal expansion and contraction. Polymers including PPS expand when heated and have a high thermal expansion coefficient. The rigid polyhedron of zirconium phosphotungstate, a negative thermal expansion material, is caused by rotational coupling at high temperatures. Specifically, its molecular structure is formed by the shared vertices of tetrahedrons and octahedrons. This polyhedral structure with shared vertices will cause rotational coupling of its shared vertices when the temperature rises, thereby changing the microscopic distance between each polyhedron, causing the material to shrink when heated on a macroscopic scale. Therefore, the thermal expansion coefficient of the composite material can be reduced by blending organic zirconium phosphotungstate with PPS resin. Its inorganic zirconium phosphotungstate particles can fill part of the voids in the resin matrix, increase the constraints on the resin molecular chains, and inhibit the thermal motion of its molecular chains, thereby reducing the thermal expansion coefficient of the composite material. In addition, if the particle size of the organic zirconium phosphotungstate is too small, it is not easy to disperse in the polymer resin matrix, while if the particle size is too large, it is easy to act as a stress concentration point in the tensile test or impact test, which greatly reduces the performance. Therefore, it is more appropriate to select a particle size of 0.5 to 3.5 μm for the organic zirconium phosphotungstate.

[0037] POE-g-GMA has active epoxy groups, and the epoxy groups of functionalized POSS and organic zirconium phosphotungstate can react with the end groups of low dielectric glass fiber, PPS resin, and PA66 resin, thereby improving the compatibility and dispersibility of low dielectric glass fiber, functionalized POSS, and organic zirconium phosphotungstate in PPS matrix resin, thereby obtaining a polyphenylene sulfide composite material with high CTI, low dielectric properties and low linear thermal expansion coefficient.

[0038] The N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide used in the present invention has a melting point of 272°C and a boiling point greater than 360°C, has good thermal stability during PPS blending, and the hindered piperidinyl group can provide antioxidant effects and improve the dyeability of the composition.

[0039] The bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate used in the present invention has a melting point of 239°C and a thermal decomposition temperature of more than 350°C, has good heat resistance and hydrolysis resistance, can provide excellent color stability and melt stability for PPS during the blending process, and can prevent thermal degradation of PPS during high temperature processes, and inhibit thermal oxidative discoloration caused by long-term extrusion processing, and also provides nitrogen oxides (NO x ) Color stability in gas environment to prevent gas fumigation discoloration.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. In order to improve the defects of polyphenylene sulfide resin such as high dielectric constant and linear thermal expansion coefficient and low CTI, the present invention reduces the dielectric constant of the polyphenylene sulfide composite material by compounding low dielectric glass fiber, functionalized POSS and POE-g-GMA, improves the CTI value of the polyphenylene sulfide composite material by PA66, and improves the compatibility and dispersibility of low dielectric glass fiber, functionalized POSS and organic zirconium phosphotungstate in PPS base resin by the epoxy group of POE-g-GMA, functionalized POSS and end group of organic zirconium phosphotungstate with low dielectric glass fiber, PPS resin and PA66 resin, thereby obtaining a polyphenylene sulfide composite material with high CTI, low dielectric performance and low linear thermal expansion coefficient.

[0042] 2. The preparation method of the polyphenylene sulfide composite material provided by the present invention has a simple process, is easy to control, has low requirements on equipment, and the equipment used is all general polymer processing equipment, with low investment, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The present invention is a flow chart of a preparation process of a polyphenylene sulfide composite material according to an embodiment of the present invention. DETAILED DESCRIPTION

[0044] In order to further understand the features, technical means and specific objectives and functions of the present invention, and analyze the advantages and spirit of the present invention, the present invention is further described by the following embodiments.

[0045] The reaction mechanism of the polyphenylene sulfide composite material of one embodiment of the present invention is as follows (see the preparation process flow chart Figure 1 ):

[0046]

[0047] Among them, R is POE-g-GMA, or functionalized POSS, or organic zirconium phosphotungstate; R1 is low dielectric glass fiber.

[0048] Reaction mechanism:

[0049] It can be seen from the above reaction formula that the epoxy groups of POE-g-GMA, functionalized POSS, and organic zirconium phosphotungstate react with the end groups of low dielectric glass fiber, PPS resin, and PA66 resin, thereby improving the compatibility and dispersibility of low dielectric glass fiber, functionalized POSS, and organic zirconium phosphotungstate in the PPS matrix resin, thereby obtaining a polyphenylene sulfide composite material with high CTI, low dielectric properties, and low linear thermal expansion coefficient.

[0050] The raw materials used in the examples and comparative examples of the present invention are as follows:

[0051] PPS resin, with a number average molecular weight of 32,000, was selected from Chongqing Jushi New Material Technology Co., Ltd.

[0052] PA66 resin, with a number average molecular weight of 25,000, was selected from Henan Shenma Nylon Chemical Co., Ltd.

[0053] Low dielectric glass fiber, dielectric constant 4.3, selected from Taishan Glass Fiber Co., Ltd.

[0054] Functionalized POSS, end groups containing epoxy groups, was selected from Hybrid Plastics Company, USA.

[0055] POE-g-GMA, with a glycidyl methacrylate grafting rate of 1.2%, was selected from Shenyang Ketong Plastic Co., Ltd.

[0056] Zirconium phosphotungstate, with a particle size of 2 μm, was selected from Ningbo Chemical Raw Materials Co., Ltd.

[0057] Sodium hydroxide was selected from Sinopharm Reagent Chemical Co., Ltd.

[0058] γ-(2,3-Epoxypropoxy)propyltrimethoxysilane is selected from Tianchang Tianchen Chemical Additive Oil Factory.

[0059] Anhydrous ethanol was selected from Sinopharm Reagent Chemical Co., Ltd.

[0060] N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, selected from Rudong Jinkangtai Chemical Co., Ltd.

[0061] Bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate is selected from Shanghai Dianyao Fine Chemical Co., Ltd.

[0062] The preparation method of the organic zirconium phosphotungstate used in the following examples and comparative examples comprises the following steps: (1) placing 100 g of zirconium phosphotungstate in a flask, then adding 1000 mL of a 0.4 mol / L sodium hydroxide solution, stirring at 60° C. for 2 h, and after stirring, washing the zirconium phosphotungstate to a pH of 7 with deionized water, and drying for later use; (2) adding 4 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 60 mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, and then adding the pretreated zirconium phosphotungstate obtained in step (1) to the solution, stirring for 1.5 h, filtering and washing, and drying at 110° C. for 3 h, to finally obtain the organic zirconium phosphotungstate.

[0063] Embodiment 1:

[0064] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0065]

[0066]

[0067] The preparation method of the polyphenylene sulfide composite material is as follows: Figure 1 , including the following steps:

[0068] (1) drying the PPS resin and PA66 resin at 110° C. for 4 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0069] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0070] (3) The mixed material prepared in step (1) is added to a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to the side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and low dielectric glass fiber is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: the temperature of zone 1 is 305° C., the temperature of zone 2 is 310° C., the temperature of zone 3 is 310° C., the temperature of zone 4 is 315° C., the temperature of zone 5 is 315° C., the temperature of zone 6 is 310° C., the temperature of zone 7 is 310° C., the temperature of zone 8 is 310° C., the die head temperature is 310° C., and the screw speed is 600 rpm.

[0071] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 50, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0072] Embodiment 2:

[0073] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0074]

[0075] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0076] (1) drying the PPS resin and PA66 resin at 80° C. for 8 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as POE-g-GMA, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0077] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0078] (3) adding the mixed material prepared in step (1) into a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) into a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber into another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of zone 1 of 285° C., a temperature of zone 2 of 290° C., a temperature of zone 3 of 290° C., a temperature of zone 4 of 295° C., a temperature of zone 5 of 295° C., a temperature of zone 6 of 290° C., a temperature of zone 7 of 290° C., a temperature of zone 8 of 290° C., a die head temperature of 290° C., and a screw speed of 200 rpm.

[0079] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 35, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0080] Embodiment 3:

[0081] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0082]

[0083] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0084] (1) drying the PPS resin and PA66 resin at 100° C. for 4 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0085] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0086] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of 300° C. in zone 1, a temperature of 305° C. in zone 2, a temperature of 305° C. in zone 3, a temperature of 310° C. in zone 4, a temperature of 310° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 305° C. in zone 7, a temperature of 305° C. in zone 8, a die head temperature of 305° C., and a screw speed of 500 rpm.

[0087] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 45, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0088] Embodiment 4:

[0089] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0090]

[0091] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0092] (1) drying the PPS resin and PA66 resin at 90° C. for 6 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0093] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0094] (3) The mixed material prepared in step (1) is added to a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to the side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and low dielectric glass fiber is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of zone 1 of 290° C., a temperature of zone 2 of 295° C., a temperature of zone 3 of 295° C., a temperature of zone 4 of 300° C., a temperature of zone 5 of 300° C., a temperature of zone 6 of 295° C., a temperature of zone 7 of 295° C., a temperature of zone 8 of 295° C., a die head temperature of 295° C., and a screw speed of 300 rpm.

[0095] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 35, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0096] Embodiment 5:

[0097] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0098]

[0099]

[0100] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0101] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0102] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0103] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 305° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 300° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.

[0104] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0105] Embodiment 6:

[0106] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0107]

[0108] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0109] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0110] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0111] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 305° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 300° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.

[0112] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0113] Embodiment 7:

[0114] This embodiment provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0115]

[0116] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0117] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0118] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0119] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 305° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 300° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.

[0120] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0121] Comparative Example 1:

[0122] This comparative example provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0123]

[0124] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0125] (1) drying the PPS resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin, POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0126] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0127] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 305° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 300° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.

[0128] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0129] Comparative Example 2:

[0130] This comparative example provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0131]

[0132]

[0133] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0134] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0135] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0136] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, and adding the mixed material prepared in step (2) to the side (fourth zone) of the parallel twin-screw extruder (eight zones in total) for melt extrusion and granulation, wherein the process parameters include: a temperature of zone 1 of 295° C., a temperature of zone 2 of 300° C., a temperature of zone 3 of 300° C., a temperature of zone 4 of 305° C., a temperature of zone 5 of 305° C., a temperature of zone 6 of 300° C., a temperature of zone 7 of 300° C., a temperature of zone 8 of 300° C., a die head temperature of 300° C., and a screw speed of 400 rpm.

[0137] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0138] Comparative Example 3:

[0139] This comparative example provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0140]

[0141] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0142] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0143] (2) The mixed material prepared in step (1) is added to a parallel twin-screw extruder through a feeder, and organic zirconium phosphotungstate is added to the side (fourth zone) of the parallel twin-screw extruder (a total of eight zones), and low dielectric glass fiber is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: the temperature of zone 1 is 295° C., the temperature of zone 2 is 300° C., the temperature of zone 3 is 300° C., the temperature of zone 4 is 305° C., the temperature of zone 5 is 305° C., the temperature of zone 6 is 300° C., the temperature of zone 7 is 300° C., the temperature of zone 8 is 300° C., the die head temperature is 300° C., and the screw speed is 400 rpm.

[0144] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0145] Comparative Example 4:

[0146] This comparative example provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0147]

[0148] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0149] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0150] (2) adding the functionalized POSS and the organic zirconium phosphotungstate into another mixer and mixing;

[0151] (3) adding the mixed material prepared in step (1) to a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to another side (third zone) for melt extrusion and granulation, wherein the process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 305° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 300° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.

[0152] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0153] Comparative Example 5:

[0154] This comparative example provides a polyphenylene sulfide composite material, which is prepared from the following raw materials in parts by weight:

[0155]

[0156] The preparation method of the polyphenylene sulfide composite material comprises the following steps:

[0157] (1) drying the PPS resin and PA66 resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and PA66 resin, as well as the POE-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a mixer for mixing;

[0158] (2) adding the mixed material in step (1) into a parallel twin-screw extruder via a feeder, adding functionalized POSS to the side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and adding low dielectric glass fiber to the other side (third zone) for melt extrusion and granulation, wherein the process parameters include: a zone temperature of 295°C, a zone temperature of 300°C, a zone temperature of 300°C, a zone temperature of 300°C, a zone temperature of 405°C, a zone temperature of 305°C, a zone temperature of 600°C, a zone temperature of 300°C, a zone temperature of 300°C, a zone temperature of 800°C, a die head temperature of 300°C, and a screw speed of 400 rpm.

[0159] The screw shape of the parallel twin-screw extruder is a single-line thread, the ratio of the screw length L to the diameter D L / D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.

[0160] The following is a list of raw material compositions of the examples and comparative examples (Table 1).

[0161] Table 1 List of weight parts of raw materials for examples and comparative examples

[0162]

[0163]

[0164] The addition amount of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate in the above examples and comparative examples is 0.25 parts.

[0165] Examples 1 to 7 are for preparing polyphenylene sulfide composite materials by adjusting the addition amount of PPS resin, PA66 resin, low dielectric glass fiber, functionalized POSS, POE-g-GMA, and organic zirconium phosphotungstate. Comparative Example 1 is for preparing a polyphenylene sulfide composite material without adding PA66 resin, Comparative Example 2 is for preparing a polyphenylene sulfide composite material without adding low dielectric glass fiber, Comparative Example 3 is for preparing a polyphenylene sulfide composite material without adding functionalized POSS, Comparative Example 4 will not add POE-g-GMA to prepare a polyphenylene sulfide composite material, and Comparative Example 5 will not add organic zirconium phosphotungstate to prepare a polyphenylene sulfide composite material.

[0166] The polyphenylene sulfide composite materials prepared in the above examples and comparative examples were subjected to the following performance tests:

[0167] Tensile properties: tested according to GB / T 1040-2006 standard, the tensile rate is 50mm / min.

[0168] CTI test: 3mm×100mm×100mm square plate was tested. During the test, the mass fraction of ammonium chloride solution used was 0.1% and the resistivity was 385Ω·cm.

[0169] Dielectric constant: Tested according to GB / T 5597-1999 standard, the test frequency is 1GHz. For this composite material, the lower the dielectric constant, the better.

[0170] Linear thermal expansion coefficient: The linear thermal expansion coefficient of the composite material was tested using a static thermomechanical analyzer TMA Q400 (TA Instruments, USA). Specifically, the change in the vertical dimension of the composite columnar sample with temperature was measured in the test temperature range of 40 to 300°C, and the heating rate was 5°C / min.

[0171] The performance test results are shown in Table 2.

[0172] Table 2 Performance of polyphenylene sulfide composite materials of embodiments and comparative examples

[0173]

[0174] From Table 2 we can see that:

[0175] As the amount of low dielectric glass fiber added increases, the tensile strength of the polyphenylene sulfide composite increases. This is because the low dielectric glass fiber can reinforce the PPS composite.

[0176] As the amount of PA66 added increases, the CTI value of the polyphenylene sulfide composite material gradually increases. This is because polyphenylene sulfide (PPS) is a thermoplastic material with a benzene ring in the main chain, and its carbon-forming ability is very strong. The CTI of pure PPS is only 150V, and the CTI can usually be improved by adding materials with poor carbon-forming ability to form an alloy. Polyamide 66 (PA66) is a polymer material without a benzene ring in the main chain, and its carbon-forming ability is poor. The CTI of pure PA is as high as 600V, and it has a certain compatibility with PPS, and the CTI of PPS can be improved by blending with PPS.

[0177] With the increase of the addition amount of POE-g-GMA, low dielectric glass fiber and functionalized POSS, the dielectric constant of polyphenylene sulfide composite material gradually decreases. This is because low dielectric glass fiber belongs to a glass system with a high boron content, and has the characteristics of low density, low dielectric constant and low dielectric loss. The low dielectric glass fiber adjusts the glass chemical composition, reduces the CaO content, increases the BO content, and introduces a small amount of TiO to achieve the purpose of reducing the dielectric constant; polyhedral oligomeric silsesquioxane (POSS) has a cage-type nanostructure, which has a large free volume, high porosity and low molecular polarizability, so the dielectric constant of POSS is 2 to 2.5 (test frequency is 1GHz); POE-g-GMA molecules do not have unsaturated double bonds, which makes the electron cloud distribution of the molecule relatively stable. Under the action of the electric field, the electron cloud is not prone to violent displacement and polarization, so the dielectric constant is low. In addition, there is a certain amount of short side chains in the POE molecular structure, and the presence of these short side chains increases the steric hindrance of the molecule and limits the close stacking of the molecular chain. The gaps between molecular chains increase, reducing the interactions between molecules, which reduces the polarization of molecules under the action of the electric field, leading to a decrease in the dielectric constant.

[0178] As the amount of organic zirconium phosphotungstate increases, the linear thermal expansion coefficient of the polyphenylene sulfide composite material gradually decreases. This is because the organic zirconium phosphotungstate can reduce the thermal expansion coefficient of the composite material after being blended with PPS resin. Its inorganic zirconium phosphotungstate particles can fill some of the gaps in the resin matrix and increase the constraints on the resin molecular chain, inhibiting the thermal motion of its molecular chain, thereby reducing the thermal expansion coefficient of the composite material.

[0179] In summary, by adjusting the addition amounts of PPS resin, PA66 resin, low dielectric glass fiber, functionalized POSS, POE-g-GMA, and organic zirconium phosphotungstate, with the coordinated cooperation of various additives, the polyphenylene sulfide composite material of the present invention with excellent mechanical properties, high CTI, low dielectric properties and low linear thermal expansion coefficient can be obtained.

[0180] Compared with Example 7, Comparative Example 1 is a polyphenylene sulfide composite material prepared without adding PA66 resin. Since polyphenylene sulfide (PPS) is a thermoplastic material containing benzene rings in the main chain, it has a strong carbon-forming ability. The CTI of pure PPS is only 150V, and the CTI can usually be improved by adding materials with poor carbon-forming ability to form an alloy. Polyamide 66 (PA66) is a polymer material without benzene rings in the main chain, and has poor carbon-forming ability. The CTI of pure PA is as high as 600V, and it has a certain compatibility with PPS, and the CTI of PPS can be improved by blending with PPS. Therefore, the CTI value of Comparative Example 1 is lower than that of Example 7.

[0181] Compared with Example 7, Comparative Example 2 is a polyphenylene sulfide composite material prepared without adding low dielectric glass fiber. Since low dielectric glass fiber can strengthen the PPS composite material, and low dielectric glass fiber belongs to a glass system with a high boron content, it has the characteristics of low density, low dielectric constant and low dielectric loss. Therefore, the tensile strength of Comparative Example 2 is lower than that of Example 7.

[0182] Compared with Example 7, Comparative Example 3 is a polyphenylene sulfide composite material prepared without adding functionalized POSS. Since polyhedral oligomeric silsesquioxane (POSS) has a cage-type nanostructure, it has a large free volume, high porosity and low molecular polarizability, so the dielectric constant of POSS is 2 to 2.5 (test frequency is 1 GHz). Therefore, the dielectric constant of Comparative Example 3 is higher than that of Example 7.

[0183] Compared with Example 7, Comparative Example 4 will not add POE-g-GMA to prepare a polyphenylene sulfide composite material, because POE-g-GMA has an active epoxy group, and the epoxy groups of functionalized POSS and organic zirconium phosphotungstate can react with the end groups of low dielectric glass fiber, PPS resin, and PA66 resin, thereby improving the compatibility and dispersibility of low dielectric glass fiber, functionalized POSS, and organic zirconium phosphotungstate in PPS substrate resin, thereby obtaining a polyphenylene sulfide composite material with high CTI, low dielectric properties, and low linear thermal expansion coefficient. Therefore, the tensile strength of Comparative Example 4 is lower than that of Example 7, and the dielectric constant of Comparative Example 4 is higher than that of Example 7.

[0184] Compared with Example 7, Comparative Example 5 does not add organic zirconium phosphotungstate to prepare the polyphenylene sulfide composite material. Since the organic zirconium phosphotungstate can reduce the thermal expansion coefficient of the composite material after being blended with PPS resin, its inorganic zirconium phosphotungstate particles can fill part of the gaps in the resin matrix, increase the constraints on the resin molecular chains, and inhibit the thermal motion of the molecular chains, thereby reducing the thermal expansion coefficient of the composite material. Therefore, the linear thermal expansion coefficient of Comparative Example 5 is higher than that of Example 7.

[0185] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0186] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A polyphenylene sulfide composite material, characterized in that: It is prepared from the following raw materials in parts by weight: 60-70 parts of PPS resin, 30-40 parts of PA66 resin, The total weight of PPS resin and PA66 resin is 100 parts. The functionalized POSS is a functionalized polyhedral cage-type oligomeric silsesquioxane; and the POE-g-GMA is a copolymer of ethylene and octene grafted with glycidyl methacrylate.

2. The polyphenylene sulfide composite material according to claim 1, characterized in that: The number average molecular weight of the PPS resin is 28,000 to 36,000.

3. The polyphenylene sulfide composite material according to claim 1, characterized in that: The number average molecular weight of the PA66 resin is 22,000 to 28,000.

4. The polyphenylene sulfide composite material according to claim 1, characterized in that: The dielectric constant of the low dielectric glass fiber is not higher than 4.

5.

5. The polyphenylene sulfide composite material according to claim 1, characterized in that: The terminal groups of the functionalized POSS include epoxy groups.

6. The polyphenylene sulfide composite material according to claim 1, characterized in that: The glycidyl methacrylate grafting rate of the POE-g-GMA is 1.0-1.4%.

7. The polyphenylene sulfide composite material according to claim 1, characterized in that: The particle size of the organic zirconium phosphotungstate is 0.5-3.5 μm.

8. The polyphenylene sulfide composite material according to any one of claims 1 to 7, characterized in that: The preparation process of the organic zirconium phosphotungstate is as follows: (1) adding zirconium phosphotungstate to a sodium hydroxide solution, mixing and stirring, washing the zirconium phosphotungstate with water until it is neutral, and drying for later use; (2) adding the zirconium phosphotungstate obtained in step (1) to a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, stirring, filtering and washing, and drying to obtain the organic zirconium phosphotungstate.

9. A method for preparing the polyphenylene sulfide composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) drying the PPS resin and the PA66 resin, and then mixing with the POE-g-GMA, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate; (2) mixing the functionalized POSS and the organic zirconium phosphotungstate; (3) adding the mixed material prepared in step (1) into a parallel twin-screw extruder via a feeder, adding the mixed material prepared in step (2) to one side of the parallel twin-screw extruder, and adding the low dielectric glass fiber to the other side for melt extrusion and granulation; Wherein, the drying temperature in step (1) is 80-110° C., and the drying time is 4-8 hours; and / or, the process parameters of the parallel twin-screw extruder in step (3) include: zone one temperature of 285-305° C., zone two temperature of 290-310° C., zone three temperature of 290-310° C., zone four temperature of 295-315° C., zone five temperature of 295-315° C., zone six temperature of 290-310° C., zone seven temperature of 290-310° C., zone eight temperature of 290-310° C., die head temperature of 290-310° C., and screw speed of 200-600 rpm.

10. The preparation method according to claim 9, characterized in that: The screw shape of the parallel twin-screw extruder is a single-thread; and / or the ratio L / D of the screw length L and diameter D of the parallel twin-screw extruder is 35 to 50; and / or the screw of the parallel twin-screw extruder is provided with more than one meshing block area and more than one reverse thread area.

Citation Information

Patent Citations

  • High-precision low-overflow low-warpage low-dielectric PPS modified material and preparation method thereof

    CN112679956A

  • Low-dielectric PPS / PMP composite material and preparation method thereof

    CN112694753A

  • Modified polyphenylene sulfide resin and preparation method thereof

    CN101619168A

  • Thermoplastic resin composite material and preparation method thereof

    CN105907095A

  • Negative thermal expansion material and composite material including the same

    CN108025915A